Patient and public involvement in contemporary large intensive care trials: A meta‐epidemiological study. Issue 3 (28th December 2022) - Estrup, Stine; Barot, Emily; Mortensen, Camilla Bekker; Anthon, Carl Thomas; Crescioli, Elena; Kjær, Maj‐Brit Nørregaard; Vesterlund, Gitte Kingo; Bruun, Camilla Rahbek Lysholm; Collet, Marie Oxenbøll; Rasmussen, Bodil Steen; Sivapalan, Praleene; Poulsen, Lone Musaeus; et al.
Abstract: Background: Patient and public involvement in randomised clinical trials has received increased focus, including in intensive care trials, but the frequency, method and extent is unknown. This meta‐epidemiological study investigated patient and public involvement in contemporary, large ICU trials. Methods: We systematically searched PubMed for large (≥225 randomised patients), contemporary trials (published between 1 January 2019 and 31 January 2022) assessing interventions in adult patients in ICU settings. Abstracts and full‐text articles were assessed independently and in duplicate. Data were extracted using a pre‐defined, pilot‐tested data extraction form with details on trials, patient and public involvement including categories and numbers of individuals involved, methods of involvement, and trial stage(s) with involvement. Trials authors were contacted as necessary. Results: We included 100 trials, with 18 using patient and public involvement; these were larger and conducted in more centres than trials without patient and public involvement. Among trials with patient and public involvement, patients (in 14/18 trials), clinicians (13 trials), and family members (12 trials) were primarily involved, mainly in the development of research design (15 trials) and development of research focus (13 trials) stages and mostly by discussion (12 trials) and solo interviews (10 trials). A median of 65 individuals (range 1–6894) were involved. Conclusions: We found patient and public involvement in a fifth of large, contemporary ICU trials. Primarily patients, families, and clinicians were included, particularly in the trial planning stages and mostly through interviews and discussions. Increased patient and public involvement in ICU trials is warranted.